TP5.2.13 Perceived risk of pre-operative abdominal aortic aneurysm rupture due to pulmonary function testing: all blown out of proportion?. (28th October 2021) - Badawy, Ayman; Stupalkowska, Weronika; Chaudhuri, Arindam
Abstract: Aim: Though contraindicated in some respiratory laboratories due to a perceived increased risk of aneurysm rupture, pulmonary function tests (PFT) and cardiopulmonary exercise tests (CPET) are used commonly in preoperative assessment of patients with abdominal aortic aneurysm (AAA) considered for elective repair. We examine whether preoperative PFT/CPET are associated with increased AAA rupture risk. Methods: A retrospective analysis of a prospective database of patients with AAA ≥50mm who had PFT/CPET/both as part of their preoperative assessment from November 2012 to December 2020 in a single vascular hub before elective AAA repair (open/endovascular). Patients with AAA <50mm, or those who did not have PFT/CPET preoperatively were excluded from analysis. Baseline demographics, AAA size, type of repair, time from PFT/CPET to repair, rupture rate and 30-day post-operative mortality are presented. Results: A total of 410 patients (mean age 74 ± 8 years, 361 (88%) male) were included in the analysis. The mean AAA size was 63 ±11mm. 350 (85%) patients underwent endovascular repair. 220 (53%) patients had PFT, 69 (17%) had CPET and the remaining 121 (30%) had both PFT/CPET preoperatively. The median time from PFT/CPET to repair was 36 days (IQR 48 days), with no preoperative AAA rupture in this cohort. 30-day post-operative mortality was 3%. Conclusions: This study strongly suggests that PFT and CPET are not associated with increased risk of AAA rupture and are therefore safe for assessing respiratory function in patients considered for AAA repair without adding to pre-operative rupture risk.